Polemic of Passenger Luggage Import Policy: Impact Analysis, Implementation, and Legal Challenges in Indonesia - Sapsudin, Asep; Agustin, Hilma Aulia; Gumay, Febrianti (Research Horizon, 2025)
Indonesia’s passenger luggage import policy has sparked public debate due to its impact on economic stability and compliance. This study aims to analyze the implementation, impacts, and legal challenges of the policy regulating goods brought by passengers and migrant workers. A normative legal approach was used to examine the legal framework, while an empirical approach involved interviews with customs officers and migrant workers, alongside analysis of customs declaration data from March to June 2024. The findings reveal that the policy streamlines customs processes and increases state revenue through duties, with monthly collections rising by approximately 10%. However, it faces challenges, including inconsistent enforcement, public unawareness of duty-free limits, and increased costs for small businesses reliant on imported goods. Interviews indicate that 60% of migrant workers were unaware of the regulations, contributing to compliance issues. The policy supports domestic industries but risks trade tensions with partner countries. In conclusion, while the policy enhances economic protection, it requires improved public awareness campaigns and enforcement mechanisms to address legal uncertainties and minimize negative impacts on small businesses, ensuring a balance between economic benefits and fair implementation for stakeholders.